Robust Switched H ∞ Control of T-S Fuzzy-Based MRF Suspension Systems Subject to Input Saturation and Time-Varying Delay - Gao, Zhijiang; Wong, Pak Kin; Zhao, Jing; Yang, Zhixin; Huang, Yingbo; Na, Jing (IEEE transactions on industrial electronics (1982), 2024)
This article focuses on solving the optimal control problem for magnetorheological fluid (MRF)-based semiactive suspension (SAS) systems with input saturation and time-varying delay. A robust switched H ∞ method is proposed in this work based on the Takagi-Sugeno (T-S) fuzzy theory. A novel hybrid model that incorporates both the fluid flow mechanism (FFM) and hysteresis phenomenon model (HPM) is adopted to separate the passive and active components of the MRF damper. Under such a framework, the convex and reciprocally convex approaches are used to transform the features of input saturation and time-varying delay into linear matrix inequality conditions. Furthermore, a Lyapunov-Krasovskii function is employed to guarantee the stability of the MRF-SAS system subject to input saturation and time-varying delay. Finally, the effectiveness of the proposed method is validated via a numerical example of an MRF-SAS system. The results show that the proposed controller indicates good dynamic performance for the MRF-SAS system with input saturation and time-varying delay.